PRESCRIPTION WRITING PRACTICES AND ERRORS IN PRESCRIPTIONS CONTAINING CARDIOVASCULAR DRUGS ESPECIALLY ACE INHIBITORS IN KARACHI, PAKISTAN - Nesar, Shagufta; Shoaib, Muhammad Harris; Rahim, Najia; Iffat, Wajiha; Shakeel, Sadia; Bibi, Rehana (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: This is the first study related to the prescribing errors in cardiovascular prescription drugs especially Angiotensin converting enzyme inhibitors (ACEIs) conducted with the aim to identify the prescribing errors in ACEIs prescriptions and to determine how to reduce these errors. Methods: The study period was September' 2012 till September' 2013. A total of 460 prescriptions containing ACE inhibitor drugs were retrospectively analyzed to identify the common errors in them after collecting from different outpatient settings of Karachi, Pakistan. Results: The extent of occurrence of errors was calculated; the highest number of the prescriptions (94.34%) failed to mention the patient's weight and in least proportion of the prescriptions (0.43%) prescriber signature was not mentioned. The drug-drug interaction was found in 80.65% of prescriptions. Only the brand name of the drug was mentioned in all the prescriptions. The main reason of prescription errors was maximum numbers of patients, less knowledge related to prescription writing guidelines to prescribers, and lack of pharmacy services. Conclusions: We concluded from this study, that there is a high percentage of prescription errors in outpatient settings. The only solution is that the physicians should be provided with the educational training to improve their prescription writing skills according to World Health Organization guidelines for prescription writing or other recognized and published standards. The computerized physicians order entry system should be introduced. The pharmacist can also play a vital role in minimizing and preventing these prescription errors. The health care system without pharmacists is unable to cope effectively. Keywords: Angiotensin converting enzyme inhibitors, Outpatients, Prescriptions, Prescribing error , Karachi. Â Â Â